Method for isolation of PCR-ready genomic DNA from zebrafish tissues. (November 2007) - Meeker, Nathan D.; Hutchinson, Sarah A.; Ho, Linh; Trede, Nikolaus S.
Here we describe a method for the isolation of PCR-ready genomic DNA from various zebrafish tissues that is based on a previously published murine protocol. The DNA solutions are of sufficient quality to allow PCR detection of transgenes from all commonly used zebrafish tissues. In sperm, transgene amplification was successful even when diluted 1000-fold, allowing easy identification of transgenic founders. Given its speed and low cost, we anticipate that the adoption of this method will streamline DNA isolation for zebrafish research.